2021
DOI: 10.1002/mds.28550
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Kinesia Paradoxa Is Not a Paradox

Abstract: Kinesia paradoxa is defined as "the sudden transient ability of a patient with Parkinson's disease (PD) to perform a task he or she was previously unable to perform." 1 Classic accounts report how persons with PD were seen running when triggered by a life-threatening event (fire, earthquake). Even some wheelchair-bound patients with advanced disease could run. 2 Apparently, these patients could use locomotor abilities no one suspected to be present. 3 Similarly, it is frequently seen that patients have difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
15
0
2
Order By: Relevance
“…A conceptual representation of this is through kinesia paradoxa in PD, where an individual with marked gait dysfunction experiences difficulty with basic tasks, such as walking, but is able to run or play sport proficiently. 13 This may differentiate the activation of cognitively driven versus emotionally driven pathways that facilitate contextually different types of movement, utilizing differing pathways through common neuroanatomical structures that correspond to a ventral and dorsal motor system. 14 The basal ganglia may be involved in switching between such pathways, 13 with the relative degeneration of the posterior putamen involved in automatic rather than goal-directed movements a potential cause of gait dysfunction in PD.…”
Section: Mechanisms Of Normal Gaitmentioning
confidence: 99%
See 1 more Smart Citation
“…A conceptual representation of this is through kinesia paradoxa in PD, where an individual with marked gait dysfunction experiences difficulty with basic tasks, such as walking, but is able to run or play sport proficiently. 13 This may differentiate the activation of cognitively driven versus emotionally driven pathways that facilitate contextually different types of movement, utilizing differing pathways through common neuroanatomical structures that correspond to a ventral and dorsal motor system. 14 The basal ganglia may be involved in switching between such pathways, 13 with the relative degeneration of the posterior putamen involved in automatic rather than goal-directed movements a potential cause of gait dysfunction in PD.…”
Section: Mechanisms Of Normal Gaitmentioning
confidence: 99%
“…13 This may differentiate the activation of cognitively driven versus emotionally driven pathways that facilitate contextually different types of movement, utilizing differing pathways through common neuroanatomical structures that correspond to a ventral and dorsal motor system. 14 The basal ganglia may be involved in switching between such pathways, 13 with the relative degeneration of the posterior putamen involved in automatic rather than goal-directed movements a potential cause of gait dysfunction in PD. 15 The cerebellum is increasingly thought to contribute to gait function, having a potential higher processing role independent of the cortices, acting on feedback, and facilitating predictive adaption of gait within the environment.…”
Section: Mechanisms Of Normal Gaitmentioning
confidence: 99%
“…Dopamine may contribute to the phenomenon of paradoxical kinesia, considering that dopaminergic mechanisms take part in regulating adaptive responses to aversive situations ( De Oliveira et al, 2014 ; Brandão et al, 2015 ). Under aversive conditions, increases in residual dopaminergic neurons firing rate in limbic parts of the basal ganglia could occur, allowing unconstrained movement ( Duysens and Nonnekes, 2021 ). Consistent with this hypothesis, in response to aversive stimulation, several authors have reported increased activation of substantia nigra and ventral tegmental area neurons and release of dopamine in the striatum ( Chiodo et al, 1979 , 1980 ; Keller et al, 1983 ; Abercrombie et al, 1989 ; Martinez et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Souques (1921), quien observó que las personas con EP eran capaces de correr aun cuando no pudieran caminar. Se ha planteado que la kinesia paradojal es un fenómeno del sistema motor (Ballanger et al, 2006) que designa un movimiento inesperado para las condiciones en que se encuentra la persona; incluso, se ha señalado que, pensando al sistema locomotor y sus vías alternativas de un modo más amplio, la kinesia paradójica no sería tan inesperada e inusual (Duysens & Nonnekes, 2021).…”
Section: Comportamiento Y Enfermedad De Parkinson: Kinesia Paradojalunclassified
“…Cabe aclara que la primera referencia así dicha a esta idea de aprovechamiento terapéutico de la kinesia paradojal se encontró solo recientemente (Duysens, & Nonnekes, 2021); aunque también se ha hablado de uso de estrategias compensatorias (Nonnekes et al, 2019) y, últimamente, su utilización terapéutica (Tosserams et al, 2021). Previamente, las descripciones del fenómeno se centraban más en lo anecdótico o como recurso de discusión para explicar el comportamiento pero no presentaban directamente esta idea central del uso terapéutico que fue el eje de la iniciativa del TdP desde su conformación en 2002.…”
Section: Desarrollo Del Producto 1 Introducción Y Objetivounclassified